Justice for All in the Americas? A Quantitative Analysis of Admissibility Decisions in the Inter-American Human Rights System - Simon Zschirnt (Laws, 2021)
The overwhelming majority of unsuccessful petitions in the Organization of American States’ Inter-American human rights system are unsuccessful because they are dismissed at the pre-admissibility or admissibility phase rather than at the merits phase. Although this preliminary screening of applications constitutes the major obstacle to petitioners seeking justice, there has been relatively little scholarly analysis of the potential interplay of legal and attitudinal factors at this phase. That is, whether this phase may be where the biases that the system has been accused of (i.e., bias against leftist regimes and a “hierarchization” of negative rights and liberties over social justice) manifest themselves. This article fills this gap in the literature by undertaking a comprehensive quantitative analysis of Inter-American Commission on Human Rights admissibility decisions that measures the impact of a broad range of factors and compares the dynamics of admissibility decisions with those of merits decisions. In so doing, it places into context backlash against the system that has led to recent changes in the system’s procedures.